Paliperidone palmitate versus oral antipsychotics in recently diagnosed schizophrenia - Schreiner, Andreas; Zink, Mathias (Schizophrenia research, 2015)
Relapse and acute exacerbation are common in schizophrenia and may impact treatment response and outcome. Evidence is conflicting in respect to superiority of long-acting injectable antipsychotic therapies versus oral antipsychotics in relapse prevention. This randomized controlled study assessed the efficacy of paliperidone palmitate versus oral antipsychotics for relapse prevention. Eligible patients with a recent diagnosis of schizophrenia (within 1-5years) were randomized 1:1 to paliperidone palmitate (n=376) or oral antipsychotic monotherapy (n=388) and entered a 2-week initial acute oral treatment phase. Patients who met predefined response criteria were eligible to enter the 24-month rater-blinded core treatment phase. Patients were evaluated for relapse, symptoms, functioning, quality of life, treatment satisfaction, and tolerability. In the core treatment phase, time to relapse was significantly longer in the paliperidone palmitate (n=352) compared with the oral antipsychotics arm (n=363): 85% of patients were relapse-free at 469 versus 249days (P=0.019). Significantly fewer patients receiving paliperidone palmitate met the relapse criteria (52 [14.8%] versus 76 [20.9%, oral antipsychotics]; P=0.032), representing a 29.4% relative risk reduction. For paliperidone palmitate, a significantly greater improvement in Positive and Negative Syndrome Scale total score on Day 8 (P=0.021) and a trend at endpoint (P=0.075) were observed. Functioning improvements were comparable between treatment arms. No new safety signals were identified. The observed time to relapse superiority of paliperidone palmitate over oral antipsychotics provides further evidence for the value of long-acting injectable antipsychotic therapies in the treatment of schizophrenia, including during the early stages of illness.